Decentralization Policy and Economic Development in Nyarusiza Sub-County Kisoro District. - Kwizera, Jemimah (Kabale University, 2025)
This study was conducted to explore the impact of decentralization on service delivery in Nyarusiza Sub-County, Kisoro District, with a specific focus on three parishes within the sub-county. The study had several objectives: to analyze the role of decentralization in promoting economic development in Nyarusiza Sub-County, to assess the impact of educational decentralization on economic growth, and to examine the relationship between agricultural decentralization and economic development in Nyarusiza Sub-County, Kisoro District. A case study approach was employed to provide an in-depth and comprehensive understanding of decentralization and its effects on service delivery. Data collection methods included questionnaires, interviews, and documentary reviews. Data was entered into a computer system and analyzed using both quantitative and qualitative techniques, with themes and subthemes developed from the study objectives. Findings revealed that educational decentralization has contributed to improved academic achievement by granting increased autonomy to communities and teachers. Respondents noted that the government, through the Ministry of Health, has emphasized prevention through mass sensitization campaigns on personal hygiene and healthy lifestyles, accounting for 25% of responses. Additionally, agricultural decentralization has led to improved services such as input supply, marketing, and rural finance for farmers. The government has also established mechanisms like farmers' cooperatives and agricultural banks to provide credit for input supply, further supporting agricultural development.